Influence of pruning time and severity on growth, fruit quality and leaf nutrient status of olive (Olea europea ) cv Frontoio - JASROTIA, AMIT; WALI, V K; BAKSHI, PARSHANT; BHUSHAN, BHARAT; SHARMA, AKASH; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during the year 2008-09 and 2009-10 comprising three dates of pruning, i.e. 1 January, 15 January, 30 January and three intensities of pruning, i.e. 20%; 25%; 30% to find out the optimum time and intensity of pruning in olive (Olea europea L.) cv Frontoio. The results revealed that maximum increase in trunk circumference (7.18%) was found in trees pruned on 1 January with 20% pruning intensity whereas maximum shoot extension growth (11.13 cm) and leaf area (3.99 cm2) was measured in trees pruned on 15 January with 25% pruning intensity. However, significantly higher chlorophyll content of 1.57 mg/g was found in trees pruned on 15 January with 30% pruning intensity. The maximum fruit quality characters, viz. size (1.76 cm), weight (2.41 g), volume (2.35cc), pulp: stone ratio (3.62) and oil content (27.03%) were observed in trees pruned on 15 January with 25% pruning intensity. The highest leaf N (1.91%), P (0.243%) and K (1.99%) was found in trees pruned on 30 January with 30% pruning intensity, 1 January with 30% pruning intensity and 15 January with 30% pruning intensity, respectively. The leaf Ca (1.70%) and Mg (0.141%) were highest in trees pruned on 1 January with 20% pruning intensity.